Value Creation of the New Baroid Plant. - Tarverdiyeva, Ramila (ADA University, 2015)
With the increasing complexity of the oil and gas wells being drilled in Caspian Sea, the majority of drilling companies are switching to Non-Aqueous types of drilling fluids (NAF). Although they guarantee improved drilling efficiency, the down side is these types of fluids is that they cannot be •mixed on platforms and require a special onshore facility - a Liquid Mud Plant (LMP). LMP's are designed to supply high volumes of drilling and completion fluids for offshore drilling rigs. These fluids are transported to the rigs by boat. The client company, Halliburton Eurasia Ltd, does not have an LMP in Azerbaijan which is a serious obstacle for the company's ability to respond to the growing demand of the drilling fluids market in the country. The market has been continuously expanding over the last 15 years and projected growth over the next 4 years is 25%, which equals $270 million1 The main goal of this Business Consulting Project (BCP) is to analyze the growth of the drilling fluids market and its requirements, to analyze the perspectives and competitive advantages of the company in the industry after the construction of an LMP. Also, the research related to this project should clarify if a new plant can increase annual revenue, how it will lead to a growth in market share, increase productivity and profitability of the company.
Business Consulting Project.
Keywords: Business; Liquid Mud Plant--Azerbaijan; Azerbaijan--Energy sector; Azerbaijan--Oil & Gas Industries.